Correlation between Preoperative Pain Duration and Percutaneous Vertebroplasty Outcome - Rad, A. Ehteshami (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: The duration of the fracture is considered by many practitioners to be an important predictor of outcome following vertebroplasty. We sought to define the impact of preprocedural pain duration on outcomes, including pain relief, improvement in function, and medication usage among patients treated with single-level vertebroplasty. MATERIALS AND METHODS: Institutional review board approval was obtained before conducting this retrospective analysis of 321 patients undergoing single-level vertebroplasty at our institution. Fractures were categorized as acute (≤6 weeks, n = 153), subacute (6–24 weeks, n = 124), and chronic (>24 weeks, n = 44). Pain NRS (0–10) scores at rest and with activity and RDS were compared among 3 groups at baseline and post procedure. Also absolute and proportional improvement of pain NRS and RDS were compared among 3 groups by using ANOVA. Linear regression was performed between preoperative pain duration and symptom improvement for each group. RESULTS: Baseline RDS and pain NRS with activity and at rest were not significantly different among groups (P = .09, .30, and .91, respectively). Mean improvement in pain NRS with activity at 1 month postvertebroplasty in acute (improvement = 4.9 ± 3.5), subacute (improvement = 4.2 ± 3.2), and chronic fractures (improvement = 4.5 ± 3.2) was similar among groups (P = .28). Mean improvement in RDS at 1 month postprocedure was 9.6, 8.3, and 9.9, for acute, subacute, and chronic fractures, respectively (P = .56). There was no strong correlation between length of pain and symptom improvement. CONCLUSIONS: The age of fracture has minimal impact on outcome following single-level vertebroplasty, with good outcomes noted among patients with acute, subacute, and chronic fractures.